Crafting Blindness: Its Organizational Construction in a First Grade School - Gobo, Giampietro (Qualitative Sociology Review, 2008)
This article is based on a case study conducted in an Italian primary school where the interactions between a sightless girl (named Jasmine, aged 8) and her classmates were extensively observed. The initial aim was to understand and describe the problems encountered by the sightless pupil, who acted in a social, organizational and physical environment which was not designed for handicapped people. However, other theoretical issues emerged during the research. The main finding was that sightlessness seems socially and organizationally constructed before it becomes a biological/physical handicap. The organizational processes through which the blindness is slowly and routinely constructed were extensively described.